2019
DOI: 10.1016/j.pharep.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of nor-wogonin (5, 7, 8-trihydroxyflavone) on human triple-negative breast cancer cells via downregulation of TAK1, NF-κB, and STAT3

Abstract: Background: Nor-wogonin, a polyhydroxy flavone, has been shown to possess antitumor activity. However, the mechanisms responsible for its antitumor activity are poorly studied. Herein, we investigated the mechanisms of nor-wogonin actions in triple-negative breast cancer (TNBC) cells. Methods: Effects of nor-wogonin on cell proliferation and viability of four TNBC cell lines (MDA-MB-231, BT-549, HCC70, and HCC1806) and two non-tumorigenic breast cell lines (MCF-10A and AG11132) were assessed by BrdU incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
0
21
1
Order By: Relevance
“…Similarly, (5, 7, 8-trihydroxyflavone (NOR-wogonin) is a polyhydroxyflavone with antitumor activity. It can significantly inhibit the proliferation of TNBC cell lines (MDA-MB-231, BT-549, HCC70, and HCC1806) compared with non-tumorigenic BC lines (MCF-10A and AG11132) through downregulating the expression of CDK1 [159]. Moreover, Galangin, another plant anticancer compound, inhibits the survival of MCF-7 cells and induces apoptosis by downregulating CDK1, CDK2, and CDK4, leading to cell-cycle arrest [160].…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…Similarly, (5, 7, 8-trihydroxyflavone (NOR-wogonin) is a polyhydroxyflavone with antitumor activity. It can significantly inhibit the proliferation of TNBC cell lines (MDA-MB-231, BT-549, HCC70, and HCC1806) compared with non-tumorigenic BC lines (MCF-10A and AG11132) through downregulating the expression of CDK1 [159]. Moreover, Galangin, another plant anticancer compound, inhibits the survival of MCF-7 cells and induces apoptosis by downregulating CDK1, CDK2, and CDK4, leading to cell-cycle arrest [160].…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…Both compounds have also exerted their anticancer activities in TNBC models in vitro and in vivo [104, 105]. Moreover, nor-wogonin was found to inhibit the expression of transforming growth factor β-activated kinase 1 (TAK1), therefore dephosphorylating STAT3 without affecting its total expression level [106]. The dopamine receptor D2 (DRD2)-targeting drug thioridazine inhibits TNBC cell self-renewal through reducing DRD2-mediated STAT3 activation [107].…”
Section: Targeting Stat3 For Tnbc Prevention and Therapymentioning
confidence: 99%
“…Studies have revealed that norwogonin owns antioxidant [ 25 ], anticancer [ 26 , 27 ], antiviral [ 28 ] and antimicrobial activities [ 29 ] as well as inhibits the cyanide-stimulated production of ROS [ 30 ]. However, whether norwogonin has protective capacities against hypoxia-induced injury remains unknown.…”
Section: Introductionmentioning
confidence: 99%